2016
DOI: 10.3390/en10010003
|View full text |Cite
|
Sign up to set email alerts
|

Deep Neural Network Based Demand Side Short Term Load Forecasting

Abstract: Abstract:In the smart grid, one of the most important research areas is load forecasting; it spans from traditional time series analyses to recent machine learning approaches and mostly focuses on forecasting aggregated electricity consumption. However, the importance of demand side energy management, including individual load forecasting, is becoming critical. In this paper, we propose deep neural network (DNN)-based load forecasting models and apply them to a demand side empirical load database. DNNs are tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
162
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 306 publications
(182 citation statements)
references
References 28 publications
1
162
0
2
Order By: Relevance
“…Meanwhile, Kuremoto successfully used Kennedy's particle swarm optimization in selecting their model parameters [18]. The work most similar to ours is Ryu et al, who found that two different types of examined DNNs performed better on short-term load forecasting of electricity than shallow neural networks and a double seasonal Holt-Winters model [19].…”
Section: Prior Worksupporting
confidence: 60%
“…Meanwhile, Kuremoto successfully used Kennedy's particle swarm optimization in selecting their model parameters [18]. The work most similar to ours is Ryu et al, who found that two different types of examined DNNs performed better on short-term load forecasting of electricity than shallow neural networks and a double seasonal Holt-Winters model [19].…”
Section: Prior Worksupporting
confidence: 60%
“…The multiple computation layers structure increases the feature abstraction capability of the network, which makes them more efficient in learning complex non-linear patterns [32]. To the best of our knowledge and according to Ryu et al [14] in 2017, only a few DNN-based load forecasting models are proposed. Recently, in 2016, Mocanu et al [1] employed, a deep learning approach based on a restricted Boltzmann machine, for single-meter residential load forecasting.…”
Section: Introductionmentioning
confidence: 99%
“…The same year (2016), Marino et al [33] presented a novel energy load forecasting methodology using two different deep architectures namely, a standard LSTM and an LSTM with sequence to Sequence architecture that produced promising results. In 2017, Ryu et al [14] proposed a DNN based framework for day-ahead load forecast by training DNNs in two different ways, using a pre-training restricted Boltzmann machine and using the rectified linear unit without pre-training. This model exhibited accurate and robust predictions compared to shallow neural network and others alternatives (i.e., double seasonal Holt-Winters model and the autoregressive integrated moving average model).…”
Section: Introductionmentioning
confidence: 99%
“…Even though our framework is independent of short-term load forecasting techniques, we use the double seasonal Holt-Winters (DSHW) [15], which is one of the popular time series load forecasting techniques. Note that, however, our method is compliant with any kind of load forecasting methods such as the newly developed deep neural network (DNN)-based model [16,17]. Then, we compute the error distribution between predicted and real load profiles, which is used to set robust margin, or called robust proportion hereafter.…”
Section: Robust Ess Operation Frameworkmentioning
confidence: 99%